Assessment of Internal Control Practices on Financial Performance of State Corporations in Kenya - Mrima, Robert; Ronald, Martin (International Journal of Finance and Accounting, 2022)
Purpose: The purpose of this study was to assess the influence of internal control practices on financial performance of state corporations in Kenya. State corporations have been identified as important drivers in accelerating national growth and2 development as well as2improving delivery of public services. However, their performance has over the years been a2matter of public2concern. Methodology: The study used descriptive research design. A study population of 561 was collected2and a sample of 234 was selected for the study randomly using Yamane (1967) formula. It involved collection of primary data on segregation of duties, transactional authorization, independent checks, documentation and records. Secondary data was collected as well to assess the performance of the state corporations. Data was obtained randomly from the corporations and analyzed using descriptive statistics and regression analysis and the outcomes were shown through tables. Findings: Upon analysis of data collected, findings showed that internal control practices significantly influenced the financial performance of state corporations in Kenya. The internal control practices had a significant influence on the financial performance of state corporations. Unique Contributions to Theory, Practice and Policy: It was concluded that these internal control factors were critical and needed to be embraced so as excellent financial performance of state corporations can be realized. The study recommended that the management should continually assess the risk, monitor control implementation, and modify controls as needed in order to identify and establish effective controls.